2006
DOI: 10.1016/s1808-8694(15)30035-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of salivary pH and volume in adults with chronic laryngopharyngitis by gastroesophageal reflux disease before and after treatment

Abstract: These findings suggest that salivary pH and volume are influenced by the presence of gastroesophageal contents and that salivary pH monitoring can potentially become a cost-effective method for diagnosing and controlling LPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Using failure to maintain alkalinization in the cervical esophagus in the diagnosis of LPR is also consistent with recent studies that show a reduction in salivary pH in LPR patients when compared to normal individuals without LPR, and a positive correlation has been shown between the presence of the laryngopharyngeal symptoms and a reduction in salivary volume. 27,28 Although we have shown that sensitivity can be improved by adding the assessment of percent time pH≥7 to dual probe monitoring, further studies will be needed to determine whether the overall accuracy is affected. In clinical practice, enhanced sensitivity often comes at the expense of reduced specificity.…”
Section: Discussionmentioning
confidence: 97%
“…Using failure to maintain alkalinization in the cervical esophagus in the diagnosis of LPR is also consistent with recent studies that show a reduction in salivary pH in LPR patients when compared to normal individuals without LPR, and a positive correlation has been shown between the presence of the laryngopharyngeal symptoms and a reduction in salivary volume. 27,28 Although we have shown that sensitivity can be improved by adding the assessment of percent time pH≥7 to dual probe monitoring, further studies will be needed to determine whether the overall accuracy is affected. In clinical practice, enhanced sensitivity often comes at the expense of reduced specificity.…”
Section: Discussionmentioning
confidence: 97%
“…Twenty three patients with either GERD or larygnopharyngeal reflux were enrolled in a 12 wk study to assess the change in the salivary pH when administered omeprazole 20 mg twice daily by mouth. Prior to beginning therapy, the average salivary pH was 7.15, but this increased to 7.58 following 12 wk of therapy [42] . Although this was a statistically significant increase in pH, the physiological pH of salivary acid is generally about 8.0.…”
Section: Ppis and Pneumonia-pathophysiologymentioning
confidence: 99%
“…A study conducted by Eckley [42] took this concept one step further. Twenty three patients with either GERD or larygnopharyngeal reflux were enrolled in a 12 wk study to assess the change in the salivary pH when administered omeprazole 20 mg twice daily by mouth.…”
Section: Ppis and Pneumonia-pathophysiologymentioning
confidence: 99%
“…Accessible body fluids such as saliva represent an interesting medium for the realization of body-sensing, as these fluids also contain important personal physiological information [13][14][15][16][17][18][19][20]. Continuous monitoring of pH in saliva would be extremely beneficial for maintaining healthy mouth conditions, e.g., degradation of tooth enamel [21] and detection of Gastroesophageal Reflux Disease (GERD) [22][23][24], as well as drug activity, as in some cases this can depend on saliva pH [17].…”
Section: Introductionmentioning
confidence: 99%